Book cover Radical Solutions for Digital Transformation in Latin American Universities pp 179–195Cite as Artificial Intelligence as a Support Philosophy for Change: Comunidad Andina Case Study - Yabar Vega, Ben Y. P.; Diaz Zelada, Yvan F. (Lecture Notes in Educational Technology, 2023)
The present study aims to observe the development of artificial intelligence in Bolivia, Colombia, Ecuador and Peru, countries that make up the Comunidad Andina, a supranational organization located in South America; likewise, understand the contribution of artificial intelligence as a philosophical component in the dynamics of change that are occurring in the different productive sectors of the aforementioned countries. In this sense, different sectors of each member country of the Comunidad Andina are analyzed. By inserting artificial intelligence in these four countries, it has been transforming reality in the different productive sectors through technology, self-learning and organizational knowledge, all this is modifying business and organizational paradigms, generating new ways of conceiving of companies. Economic organizations, understanding this as a new philosophical conception of organizations. This study uses the official reports and journalistic notes on the situation by productive sectors, issued by the competent government agencies and by the companies themselves, and based on the information collected, a comparative analysis is carried out between the countries that make up the Comunidad Andina, where the component “Economic model” is essential. The study finally aims to offer a basic document that serves as a diagnosis of artificial intelligence and how this variable has been transforming public thinking and policies aimed at the development of productive sectors and business conception.
Keywords: artificial Intelligence; comunidad Andina; philosophy; productive sectors; Scopus(2)